An evaluation on different origins of natural organic matters using various anodes by electrocoagulation. (April 2015) - Ulu, Feride; Barışçı, Sibel; Kobya, Mehmet; Sillanpää, Mika
Highlights: EC process is effective on treatment of different NOM sources. Aluminum anode was showed the best short term performance. The lowest effluent concentration was obtained by hybrid electrode. SUVA value was reduced to below 2 for three NOM sources studied. The floc size and zeta potential were affected by the change of pH. Abstract: In this investigation, natural organic matters (NOM) of different origins (commercial, terrestrial and natural water) were treated by electrocoagulation (EC) process using aluminum, iron and hybrid electrodes. Electrode type effect on removal efficiency was observed for each NOM (commercial, terrestrial, and natural). The results were presented as dissolved organic carbon (DOC) (mg L −1 ) and UV/VIS absorbance (cm −1 ). The specific UV absorbance (SUVA) was determined before and after treatment of water. The lowest effluent concentration was obtained as 5.05 mg L −1 with hybrid electrode for natural NOM source at its original pH 7.3. In addition, among the metal types, the best UV-abs-254 removal efficiency was obtained as 92.4% with 0.0312 cm −1 by hybrid electrode at the end of the process. The color removal efficiency of water occurred successfully by Al and hybrid electrodes. Aquatic NOM source was the most resistant to EC treatment with DOC reduction of 71.1%, 59.8%, and 68.6% for Al, Fe and hybrid electrodes, respectively. Zeta potential and floc size of colloids were observed during the process for the determination of destabilization level of natural organic matters in EC process. Fast coagulation or flocculation and incipient instability were formed during electrolysis time for Al and Fe electrode, respectively. SUVA value was reduced to below 2 for three NOM sources studied. The EC process was shown to be a viable for different NOM sources with various metals.